Protein Composition of Cotton Seeds in Relation to Agro-Climatic Variation - V SANTHY; POOJA VERMA; DEBASHIS PAUL; PRATIK DHAKADE; ANJALI CHOUDHARY; VN WAGHMARE (Seed Research, 2025)
Cotton, globally grown as a fibre crop, is also popular as oil and protein source, which is obtained from cotton seed. An investigation on seed protein content was done in popular cotton cultivars released by ICAR– Central Institute for Cotton Research. Twelve cultivars belonging to three cultivated species (G. hirsutum, G. arboreum and G. barbadense), seeds of which were produced in different locations (Central, North, and South cotton growing regions), were subjected to determination of tris-soluble and seed storage protein fractions. The laboratory investigation was conducted at one location after collecting seeds of same genotypes grown in other locations in the same season for comparing their protein content. Concentration of tris-soluble protein and sequentially extracted storage protein fractions were determined by Bradford assay. Significant variation was observed for tris-soluble and storage protein fractions among genotypes in each location and showed varied relations with seed index in G. arboreum and G. barbadense. Among the storage fractions, globulin fraction was highest followed by albumins in the studied cultivars. Though the values of each protein component differed widely in different location, the genotypes maintained their rank for both tris-soluble protein content as well as seed storage fraction content irrespective of the location where the seeds were produced.